Failure analysis of SUS304 sheet during hydro-bulging based on GTN ductile damage model. Issue 1 (September 2016) - Zhang, W.; Cong, S.
Abstract Stainless steel sheet has a good forming performance due to its perfect strain hardening behavior. In order to predict the hydro-formability of stainless steel sheet SUS304, Gurson-Tvergaard-Needleman (GTN) ductile damage model is used to describe the failure behavior under the condition of complicated stress state. GTN damage parameters were identified by the comparison between simulation and experiments according to the hybrid methods including scanning electron microscope (SEM), Plackett-Burman design (PBD), and response surface methodology (RSM). Then, verification of the obtained damage parameters by experimental researches on die-less hydro-bulging of ellipsoidal shell and sheet hydro-bulging was carried out, and the hydro-formability and failure behavior were mainly discussed. It is shown that the GTN ductile damage model can be applied to evaluate the fracture during hydro-bulging. It is also experimentally proved that the hybrid method containing SEM, PBD, and RSM is a feasible to predict the damage parameters.